Ancient fires enhance Amazon forest drought resistance - Vedovato, Laura B.; Carvalho, Lidiany C. S.; Aragão, Luiz E. O. C.; Bird, Michael; Phillips, Oliver L.; Alvarez, Patrícia; Barlow, Jos; Bartholomew, David C.; Berenguer, Erika; Castro, Wendeson; Ferreira, Joice; França, Filipe M.; et al. (Frontiers in Forests and Global Change, 2023)
Drought and fire reduce productivity and increase tree mortality in tropical forests. However, fires also produce pyrogenic carbon (PyC), which persists in situ for a long time, and represents a legacy of past fires, potentially improving soil fertility, water holding capacity, and select for the survival and recruitment of certain tree life-history (or successional) strategies. We investigated how PyC is correlated with physicochemical soil properties, wood density, aboveground carbon (AGC) dynamics and affects forest resistance to severe drought. To achieve our aim, we used an Amazon-wide, long-term plot network, in forests without known recent fires, integrating site-specific measures of forest dynamics, soil properties and a unique soil PyC concentration database. We found that forests with higher concentrations of soil PyC had both higher soil fertility and lower wood density. Soil PyC was not associated with AGC dynamics in non-drought years. However, during extreme drought events (10% driest years), forests with higher concentrations of soil PyC experienced lower reductions in AGC gains (woody growth and recruitment), with this drought-immunising effect increasing with drought severity. Forests with a legacy of past fires are therefore more likely to continue to grow and recruit under increased drought severity. Forests with high soil PyC concentrations (third quartile) had 3.8% greater AGC gains under mean drought, but 33.7% greater under the most extreme drought than forests with low soil PyC concentrations (first quartile), offsetting losses of up to 0.68 Mg C ha-1yr-1 of AGC under extreme drought events. This suggests that past fires have legacy effects on current forest dynamics, by altering soil fertility and favouring establishment of earlier successional tree species capable of continued growth and recruitment during droughts. Therefore, mature forest that experienced fires centuries or millennia ago may have greater resistance to current short-term droughts.